Rectangular dark pulses in all-normal dispersion fiber oscillator. (March 2022) - Paul, Nitish; Singh, C.P.; Gupta, P.K.; Bhuvnesh,; Mukhopadhyay, P.K.; Bindra, K.S.
Highlights: Shown rectangular dark pulses in a simple linear standing wave all-fiber cavity. Studied reverse saturable absorption behaviour of nonlinear optical loop mirror. New regime of rectangular dark pulses is observed experimentally. Numerical simulations show rectangular dark pulse formation. An ansatz is proposed and derived relations between pulse and cavity parameters. Abstract: We report the generation of rectangular dark pulses (RDPs) in ytterbium (Yb) doped fiber laser using a nearly 50:50 coupler based nonlinear optical loop mirror (NOLM) in a simple linear standing wave cavity. Width of the dark pulse decreases with increase in the pump power whereas depth of the rectangular pulse profile remains constant. The nonlinear reflectance characteristics of the NOLM used in the cavity has been experimentally investigated to understand its role in formation of RDPs. Numerical simulations were performed to show the evolution of dark pulses in a fiber oscillator in all normal dispersion configuration. Both experimental and numerical simulations indicate that reverse saturable absorption supports formation of dark pulses. With increase in the saturation energy, width of RDP was found to decrease in line with the experimental observations. Further, an ansatz is proposed to model RDPs. The ansatz is used in cubic quntic Ginzburg-Landau equation to establish relationship between pulse parameters and cavity parameters. Results from analytical formalism are in accordance with the experimental measurements and numerical simulations. Detailed theoretical analysis reveals that experimentally observed RDPs do not belong to domain wall type.